Understanding business research - Weathington, Bart L.; Cunningham, Christopher J. L.; Pittenger, David J. (Hoboken, N.J. : John Wiley & Sons, 2012)
Explore the essential steps for data collection, reporting, and analysis in business research. Understanding Business Research offers a comprehensive introduction to the entire process of designing, conducting, interpreting, and reporting findings in the business environment. With an emphasis on the human factor, the book presents a complete set of tools for tackling complex behavioral and social processes that are a part of data collection in industry settings. Utilizing numerous real-world examples throughout, the authors begin by presenting an overview of the research process, outlining key ideas relating to the business environment, ethics, and empirical methods. Quantitative techniques and considerations that are specific to business research, including sampling and the use of assessments, surveys, and objective measures are also introduced. Subsequent chapters outline both common and specialized research designs for business data, including: correlational research, single variable between-subjects research, correlated groups designs, qualitative and mixed-method research, between-subjects designs, between-subjects factorial designs, and research with categorical data. Each chapter is organized using an accessible, comprehensive pedagogy that ensures a fluid presentation. Case studies showcase the real-world applications of the discussed topics while critical thinking exercises and Knowledge Checks supply questions that allow readers to test their comprehension of the presented material. Numerous graphics illustrate the visual nature of the research, and chapter-end glossaries outline definitions of key terms. In addition, detailed appendices provide a review of basic concepts and the most commonly used statistical tables. Requiring only a basic understanding of statistics, Understanding Business Research is an excellent book for courses on business statistics as well as business and management science research methods at the graduate level. The book is also a valuable resource for practitioners in business, finance, and management science who utilize qualitative and quantitative research methods in their everyday work.
Frontmatter -- Overview of the Research Process. Research and Business -- Ethics and Research -- The Foundations of Research -- An Overview of Empirical Methods -- Nuts and Bolts of Research. Writing the Research Report -- Reviewing the Literature and Forming Hypotheses -- Sampling: The First Steps in Research -- Creating and Using Assessments, Surveys, and Objective Measures -- A Model for Research Design -- Common Research Designs. Correlational Research -- Between-Subjects Designs -- Single-Variable Between-Subjects Research -- Between-Subjects Factorial Designs -- Correlated-Groups Designs -- Special Research Designs. Research with Categorical Data -- Qualitative and Mixed-Methods Research -- Appendix A: Statistics Behind the Research, or, 3What Was I Supposed to Remember from My Statistics Class Anyway?4 -- Appendix B: Statistical Tables -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Management -- Research -- Methodology; Business -- Research -- Methodology; Social sciences -- Research -- Methodology; BUSINESS & ECONOMICS -- Education; Business -- Research -- Methodology; Management -- Research -- Methodology; Social sciences -- Research -- Methodology; Business -- Research -- Methodology; Management -- Research -- Methodology; Social sciences -- Research -- Methodology; Electronic books; Electronic books